Menakar Kemampuan Bernalar Kritis dan Literasi Murid SD: Studi Kasus Tulisan Refleksi Memaknai Cerita Bergambar “Ketangguhan Wisnu” - Ignatia Esti Sumarah; Bonifatius Sigit Yuniharto (Universitas Muhammadiyah Mataram, 2026)
Abstract: The significant decline in Indonesia's reading literacy scores in the 2022 PISA data, coupled with the challenges of digital disruption for elementary school students, has become a primary urgency for strengthening the School Literacy Movement (GLS). This narrative research aims to: (1) analyze and map the relevance between students' personal experiences and the indicators of critical thinking found in characters; (2) describe the linguistic profiles of the students' writing to observe how they construct ideas of resilience through word choice and language style. The research subjects were selected using a non-probability sampling technique, specifically purposive sampling, based on the criterion of narrative depth. The participants included students from grade 4 at SD Negeri Ngringin (2 students), grade 5 at SD Negeri 1 Jatilawang (9 students), and grade 6 at SD Negeri Sariharjo (2 students). The results indicate that the use of the picture storybook